2020
DOI: 10.1001/jama.2020.12866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Low Tidal Volume vs Conventional Tidal Volume on Postoperative Pulmonary Complications in Patients Undergoing Major Surgery

Abstract: IMPORTANCE In patients who undergo mechanical ventilation during surgery, the ideal tidal volume is unclear.OBJECTIVE To determine whether low-tidal-volume ventilation compared with conventional ventilation during major surgery decreases postoperative pulmonary complications. DESIGN, SETTING, AND PARTICIPANTSSingle-center, assessor-blinded, randomized clinical trial of 1236 patients older than 40 years undergoing major noncardiothoracic, nonintracranial surgery under general anesthesia lasting more than 2 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(154 citation statements)
references
References 19 publications
4
148
1
1
Order By: Relevance
“…In several trials, application of LPV in different types of surgery improved the rates of postoperative complications [ 14 , 15 , 18 ], postoperative arterial oxygenation and pulmonary function tests [ 15 ], and also decreased acute lung injury and atelectasis [ 19 ], as well as the need for reintubation [ 20 ], hemodynamic instability, and renal failure [ 21 ]. More recently, the enthusiasm for LPV has been mitigated by some studies reporting no outcome differences between low or high tidal volumes [ 22 ] and PEEP [ 23 , 24 ] during major surgeries. In addition, for fear of hypercapnia, the use of LPV strategies in cranial and spinal surgery is still debated because potentially contraindicated in neurosurgical patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several trials, application of LPV in different types of surgery improved the rates of postoperative complications [ 14 , 15 , 18 ], postoperative arterial oxygenation and pulmonary function tests [ 15 ], and also decreased acute lung injury and atelectasis [ 19 ], as well as the need for reintubation [ 20 ], hemodynamic instability, and renal failure [ 21 ]. More recently, the enthusiasm for LPV has been mitigated by some studies reporting no outcome differences between low or high tidal volumes [ 22 ] and PEEP [ 23 , 24 ] during major surgeries. In addition, for fear of hypercapnia, the use of LPV strategies in cranial and spinal surgery is still debated because potentially contraindicated in neurosurgical patients [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were received in a recent randomised clinical trial (RCT) of patients scheduled for one-lung ventilation during oesophagectomy; patients in the protective ventilation group (Vt 6 ml kg −1 PBW) had a greater need for vasopressors and also developed hypercapnia more frequently than patients in the conventional ventilation group (Vt 10 ml kg −1 PBW) [ 24 ]. Among adult patients undergoing major surgery, intraoperative ventilation with low tidal volume (6 ml kg −1 PBW) compared with conventional tidal volume (10 ml·kg −1 PBW), with PEEP applied equally between groups, did not significantly reduce pulmonary complications within the first 7 postoperative days [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This view is further supported by recent trials that demonstrated no outcome improvements in patients randomized to receive lower V T . 30,31 In our analysis, the primary outcome is a composite of 11 distinct postoperative pulmonary complications, rather than a single outcome more directly related to lung injury (e.g., ARDS). It should be noted that the individual outcome events contributing to a composite outcome vary greatly on the basis of severity (i.e., ARDS vs. atelectasis) and frequency (range, 0.3 to 3.1%).…”
Section: One-lung Ventilation and Complicationsmentioning
confidence: 99%